Multiple paths towards Eco islands and blue development: Conference report. (March 2023) - Deng, Yuncheng; Čuka, Anica; Fu, Yanyan; Wu, Jiangyue
Abstract: Seas and islands cannot be separated when it comes to sustainable development. For island countries (regions), the sustainable use of marine resources is an obvious choice and a top priority. Despite the fact that many people are still affected by COVID-19, increasing attention is being given to developing island resilience as a means to adapt to many challenges, including climate change. The core concerns of island development are therefore balancing the needs of ecological protection and the sustainable use of natural resources. The Island Research Center of the Ministry of Natural Resources of China etc. organized the 2022 International Island Forum on November 10, 2022 with the theme, 'Eco Islands, Blue Development.' A hybrid conference was held to bring together representatives of government agencies, academic institutions, and experts from many countries around the world to discuss the key issues of sustainable island development.